Kecenderungan Remaja menjadi Pelaku Perundungan-Siber: Kontribusi Harga Diri dan Kesepian - Laras Bethari Ragasukmasuci; Maria Goretti Adiyanti (Faculty of Psychology, Universitas Gadjah Mada, 2019)
This study aimed to empirically test the tendency to be cyber-bullies in adolescents predicted by self-esteem and loneliness. The method used in this study is quantitative method. Research participants were adolescents with an age between 12 – 17 years, using communication devices connected to the internet and claimed to have mocked or insulted other through social network sites. There were 646 participants involved in this study. The data collection in this study used two methods, that were the list of content and scales. The scale used were the scale of tendency of being a cyber-bullies, adolecents self-esteem scale and adolescents loneliness scale. The reseach instrument was analyzed with content validity and realibility of Cronbach alpha ( =0,88, =0,90 =0,88). Data analysis used multiple regression analysis technique. The results showed that self-esteem and loneliness significantly can predicted the tendency of being a cyber-bullies in adolescents. The tendency to be a cyber-bullies was predicted by self-esteem and loneliness of 3.3%.